(3OjhGf Yaja GdOjf GdJdeSGfjs - (3SdjeGf Hf Ydj Hf YHO Gddg Hf Ydj Gdochej GdJdeSGfj, Yaja GdOjf,J (B690 (3g` s ((3CMeO Hf YHOGdfHj Hf Rjf GdOjf GdSGQj s)
(3ChdgG (B:s
(3MQa GdgeRI efYJgG GdUaGJ hGdCSeGA Cf JQi Ohf HQbY CSeGA s
(3BNQgG (B:s
(3MHj dce WHY HZjQ Jcda hGdWHY aj GdEfSGf dG jJZjQ TGhQJ bdHj HYOce aCLGHfj dG UHQ dj dG UHQ dj de CUHQ s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B193 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B270s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B158 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B802s
Keywords: (3GdCOHs